VERIFICATION of DATA INTEGRITY in CO-OPERATIVE MULTICLOUD STORAGE (International Journal of Engineering and Computer Science, 2013)
The integrity of data is ensured by the technique called Provable Data Possession (PDP) in storage outsourcing. In our paper, we deal with the construction of PDP scheme which is efficient for distributed cloud storage. This supports the scalability of service and data migration where we consider that the clients’ data is stored and maintained by the multiple cloud service providers. We introduced Cooperative PDP (CPDP) scheme based on homomorphic verifiable response and hash index hierarchy. The security of our scheme is proved based on multi-prover zero-knowledge proof system. This system satisfies the properties like completeness, knowledge soundness, and zeroknowledge. Besides we study the performance optimization mechanisms for our scheme, and particularly we present a method, to minimize the computation costs of clients and storage service providers, which is efficient for selecting optimal parameter values. We show with our experiments that our solution introduces lower computation and communication overheads in comparison with non-cooperative approaches.